2018
DOI: 10.1021/acs.langmuir.8b02287
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Biocompatible Functionalization of ZnS Nanoparticles by Catechol-Bearing Poly(2-methyl-2-oxazoline)s

Abstract: Zinc sulfide (ZnS) nanoparticles (NPs) are particularly interesting materials for their electronic and luminescent properties. Unfortunately, their robust and stable functionalization and stabilization, especially in aqueous media, has represented a challenging and not yet completely accomplished task. In this work, we report the synthesis of colloidally stable, photoluminescent and biocompatible core-polymer shell ZnS and ZnS:Tb NPs by employing a water-in-oil miniemulsion (ME) process combined with surface f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The doses for NP treatments analyzed here were selected based on dose−response curves assessed in our previous studies, which dealt with the same cells treated with different types of NPs. 18,70 Our results showed that the capacity of cells to form colonies was not significantly affected by the incubation of undoped and doped zinc sulfide NPs (Figure 12c). The decrease of viability of cells incubated with the lowest dose (10 μg/mL) of undoped ZnS, ZnS:Eu 0.1 at.…”
Section: T Y Aementioning
confidence: 82%
See 1 more Smart Citation
“…The doses for NP treatments analyzed here were selected based on dose−response curves assessed in our previous studies, which dealt with the same cells treated with different types of NPs. 18,70 Our results showed that the capacity of cells to form colonies was not significantly affected by the incubation of undoped and doped zinc sulfide NPs (Figure 12c). The decrease of viability of cells incubated with the lowest dose (10 μg/mL) of undoped ZnS, ZnS:Eu 0.1 at.…”
Section: T Y Aementioning
confidence: 82%
“…Both values are compatible with literature reports for ZnS (Zn2p 3/2 = 1022.0 eV; S2p = 161.6 eV). 17,18,21,45,47 Since it is not possible to discriminate between zinc sulfide and zinc oxide from the position of the Zn2p 3/2 peak (a representative fitting is shown in Figure 4a; the others are reported in Supporting Information, Figures S21a−S25a), the modified Auger parameter (AP, α = BE Zn2p 3/2 + KE ZnLMM , where KE is the kinetic energy of the peak) 48 was calculated. The resulting APs (2011.1−2011.5 eV, detailed values in Table 2) confirmed the presence of ZnS (AP = 2011.5 eV) 49 instead of ZnO (AP = 2009.5−2010.3 eV) 50 on all sample surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Dense PEOXA-brush coronas were successfully formed on sub-10 nm diameter, superparamagnetic Fe x O y NPs by employing nitrocatechol-terminating PEOXA ligands, significantly reducing association of serum proteins to the obtained core-shell NPs. [43][44][45][46] In a similar way, linear PMOXA adsorbates presenting similar anchors were additionally applied to functionalize ZnO and ZnS NPs (Figure 5a,b, respectively), yielding colloidally stable bioimaging tools that are inert toward biological media, [47,48] while silane-bearing PMOXAs were recently employed to fabricate organically modified silica (ORMOSIL) NPs (Figure 4c). [49][50][51]…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…b) Reproduced with permission. [ 48 ] Copyright 2018, American Chemical Society. c) Reproduced with permission.…”
Section: Functionalization Of Nanoparticlesmentioning
confidence: 99%
“…To conquer the drawbacks of PEO, peptidomimetic poly(2‐oxazoline)‐based polymers have drawn considerable attention recently because of their similar or better properties to PEO, that is, low toxicity, good hydrophilicity, biocompatibility, excellent antifouling ability, and high stability in oxidizing media . Pan et al .…”
Section: Introductionmentioning
confidence: 99%